The Integration of Artificial Intelligence in English Writing Instruction for Hospitality Students - Ni Luh Supartini; Luh Eka Susanti (CV. Rustam, 2025)
English writing proficiency is an essential skill for hospitality students, particularly in the context of the global hospitality industry, which requires professional communication with international tourists. However, many students struggle with grammar, vocabulary selection, and effective sentence structuring. Artificial Intelligence (AI) has emerged as a valuable tool in language learning, offering automated feedback, grammar correction, and stylistic suggestions. This study aims to implement AI technology in English writing instruction and analyze its effectiveness for hospitality students. The Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) was employed to design and evaluate AI-based writing instruction. Writing evaluation included both AI-assisted and non-AI tasks to distinguish the improvement from tool-dependent performance. The findings showed significant improvements in writing performance: grammar scores increased from a mean of 62 to 83 (34% improvement), vocabulary scores from 65 to 85 (31% improvement), and structure and cohesion from 60 to 82 (37% improvement). Although these gains demonstrate the potential of AI to support writing development, analysis of no-AI writing tasks indicated that part of the improvement stemmed from students’ increased ability to leverage AI feedback effectively. Overall writing proficiency improved from 64 to 84, representing 31% gain. Findings suggest that AI integration enhances writing skills, fosters interactive and adaptive learning, and aligns with the professional demands of the global hospitality industry.